Pengaruh Produksi Kelapa Sawit dan Nilai Ekspor Minyak Kelapa Sawit terhadap Produk Domestik Regional Bruto (PDRB) Sektor Pertanian Provinsi Kalimantan Selatan - Nuraisyah Mughniyati; Chairul Saroni (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2023)
This study aims to determine the influence of oil palm production and the export value of palm oil (crude palm oil) on the GRDP of South Kalimantan Province in the agricultural sector. This research is a multiple linear regression analysis method using eciews9 (years 2004 – 2018). The study's results indicate that the production of palm oil and the export value of crude palm oil in South Kalimantan Province together have a positive and significant effect on the GRDP of the agricultural sector in South Kalimantan Province.